Improving commissioning through design thinking. Issue 4 (2nd October 2018) - Mintrom, Michael; Thomas, Madeline
Abstract: Public policies and programs are intended to improve the lives of citizens. Considerable efforts are currently being made to utilize evidence, conduct experiments, and use program monitoring to increase the likelihood that policies and programs will generate intended effects. We explore the neglected connection between design thinking and commissioning of public services and make a general argument for how design thinking can contribute to more effective commissioning. We use the case of charter schooling to show how acquiring and sharing knowledge of local contexts can improve service design and delivery. We conclude that paying greater attention to local collaboration and service enhancement through the application of design thinking can improve commissioning and contribute significantly to the pursuit of desired social and economic outcomes.